Performance evaluation of m3 bottleneck based heuristic for M1M2M3 flow shop - Mohd Fidzwan, Md Amin Hamzas; Ahmad Bareduan, Salleh; Mohd Sabri, Hussin; M. J., Hasnul; Asmawi, Sanuddin; Zailani, Zainal Abidin (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.it